2014
DOI: 10.12968/bjnn.2014.10.5.219
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Alzheimer's Society in hospital: evaluation of a new support service for patients and their carers

Abstract: In collaboration with third sector organisation Alzheimer's Society, a new initiative to support patients with memory problems in a general hospital has been launched. Alzheimer's Society support workers hold two weekly drop-in sessions at Heartlands hospital to provide information and plan community follow-up visits. A service evaluation was conducted with semi-structured staff and carer interviews regarding their views on the service, and attendance data to the Alzheimer's Society sessions were recorded. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…START has been shown to be cost-effective and has been recommended for use throughout the NHS [22]. The qualitative data supports the use of PCIS but suggests that there is not a one-size-fits-all approach which can be used, as every patient with dementia and their carers will have different needs, preferences and responses [23,24].…”
Section: Results 2 3 and 4 Persisted At 24 Months Followingmentioning
confidence: 96%
See 4 more Smart Citations
“…START has been shown to be cost-effective and has been recommended for use throughout the NHS [22]. The qualitative data supports the use of PCIS but suggests that there is not a one-size-fits-all approach which can be used, as every patient with dementia and their carers will have different needs, preferences and responses [23,24].…”
Section: Results 2 3 and 4 Persisted At 24 Months Followingmentioning
confidence: 96%
“…The results are split by intervention used and whether patient or carer outcomes are presented. Five studies reported quantitative outcomes [ 18 22 ], the remaining study and service evaluation reported qualitative outcomes [ 23 , 24 ]. The quantitative results are tabulated by patient or carer outcomes in Tables 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations